Steering E-Government Projects from Failure to Success: Using Design-R eality Gap Analysis as a Mid-Implementation Assessment Tool - Lessa, Lemma; Negash, Solomon; Belachew, Mesfin (Emerging Issues and Prospects in African E-Government, 2014)
There are many e-government failures in developing countries. Most stu dies look at these after the event (post hoc), but this chapter takes an original approach to look mid-implementation (durante hoc) in order to provide recommendations for improvement. The authors chose a parti al failure/partial success land management information system being im plemented in one Ethiopian city. The project has made retrieval of lan d information quicker and simpler but is only partly implemented, and is still—on occasion—circumvented by public servants for personal gain . They used design-reality gap framework to understand why the project had partly failed. The authors used the design-reality gap analysis t o propose an action plan that would help institutionalise the system, steering it from partial failure to success. They demonstrate the valu e of this framework as a tool for mid-implementation analysis of e-gov ernment projects. The authors recommend its usage on other ongoing e-g overnment projects in developing countries.